Total Quality Management as a Paradigm of Business Success - Radoica Luburić (Journal of Central Banking Theory and Practice, 2014)
Total Quality Management denotes a path by which – both in a stable and a transitional environment, in a professional and scientific way and by applying a variety of methods and techniques, through constant improvements and involvement of all employees – one could get to a model that enables a simultaneous achievement of the top quality level on one hand, and the top management level, on the other. Total Quality Management is a paradigm of business success in the entire world because its set up, inter alia, improves internal functions of an organisation, instils confidence in customers and triggers improvement chain reactions with suppliers and stakeholders. Quality is the foundation and client orientation is the base of the entire concept of total quality management. Placing customers at the centre is the main idea behind the entire quality concept around which everything is built. Improving the capacity of an organization to understand and meet the actual customer needs, both stated and implied, is the main objective of the total quality management. Teamwork and team leadership play a specific role in the total quality management, top managers have the key responsibilities, and activities of the medium and lower level managers together with all employees are of immeasurable significance. Managing the teamwork within the total quality management is not only a requirement for its set up, development and implementation, but also for its survival. Total Quality Management is a managerial philosophy and a mode of running a business in order to achieve success.
Keywords: M00; M10; L22; 330; Customer/user satisfaction; employee involvement; process approach; Quality; Management; Continual improvements